भारतीय दर्शनको रूपरेखा - Hiriyanna, M. (My University, 2016)
This book covering a period of over thirty centuries explains the Indian thought in detail in three parts dealing respectively with the Vedic period, the early post-Vedic period and the age of the systems. The account given of several doctrines in each part generally includes a brief historical survey in addition to an exposition of its theory of knowledge, ontology and practical teaching.
Outlines of Indian Philosophy
Keywords: Nepali